ANALISIS PERKEMBANGAN PRODUKSI PENJUALAN SERTA PENAWARAN CPO DI PT AGRICINAL - Ginting, Elsa; Nurung, M.; Sugiarti, Sri (Jurnal AGRISEP, 2013)
The objective of the research is to analyze the development of production, selling, and factor of supply of CPO (Crude Palm Oil) in PT. Agricinal. The location is determined by purposive method with consideration that PT. Agricinal is one of the biggest CPO manufacture in Bengkulu Province. The development of production and selling are analyzed by using the Ratio to Moving Average and to analyze several factors of supply of CPO is used Linier Regression. The result research shows that (1) production development of CPO and its sales in PT. Agricinal is fluctuating year by year during 2005 – 2009. It is caused by selling in PT Agricinal is not based on its mass production, moreover in asking or order from the CPO customer; (2) the CPO price is the only one variable that give an effect to CPO offering in PT. Agricinal simultaneously.